Analisis Kesiapan dan Penerapan Smart Mobility di Indonesia - Zahrotul Fadilah; Bhisma Adiyansah; Rizal Aprianto (Jurnal Manajemen Informatika & Teknologi, 2025)
The advancement of the smart city concept in Indonesia has driven numerous regions to explore smart mobility as a practical response to urban transportation challenges. Smart mobility is regarded as a strategic solution due to its potential to develop transportation systems that are integrated, efficient, eco-friendly, and technology-oriented. This research aims to assess both the readiness and implementation of smart mobility across various cities and districts in Indonesia. Utilizing a Systematic Literature Review (SLR) with the PRISMA framework, the study analyzes 13 selected articles that fulfill predefined inclusion criteria. The review uncovers disparities in regional preparedness; Jakarta is considered highly ready, Mandalika falls into the conditional readiness category, while Batam remains in the early development stage. Implementation strategies also differ, with Jakarta applying a comprehensive model and Bandung adopting a more fragmented approach. Key enablers include the presence of physical and digital infrastructure, regulatory frameworks, quality transportation services, capable human resources, sufficient funding, and public awareness. On the other hand, notable challenges include financial constraints, infrastructure damage, limited coordination between institutions, low digital literacy, technical failures, and the absence of standardized regulations. Consequently, fostering collaboration among stakeholders, enhancing local capabilities, and ensuring continuous monitoring are essential steps toward achieving inclusive and sustainable smart mobility implementation in Indonesia.